Technology transfer and technological capability building: A study of textile and clothing industry of Pakistan / Nazia Nazeer - Nazia , Nazeer (2019)
The textile and clothing industry have been recognized as an important sector in Pakistan. Despite being endowed with one of the finest cottons and educated diaspora, the absence of technology policy has left the country as an exporter of low value-added cotton and textiles. Hence, this thesis examines the role of technology transfer, technological capabilities, as well as, organizational capabilities in transforming the industry from low to high value-added activities. Drawing on a sample of 503 textile and clothing firms along with 50 expert opinions, the study seeks to 1) develop knowledge accumulation typology based on trajectories and taxonomies for textile and clothing firms in Pakistan, 2) examine the significance of organizational capability on the relationship between technology transfer and technological capabilities, and firm performance. , and 3) develop technological upgrading index that takes account of the critical factors that influence technological upgrading in textile and clothing Industry of Pakistan. The results reveal that the catching-up trajectory is found non-linear and owing to the knowledge regime of the industry, firms started at different times their technology shifts. Large firms are mostly locked in at the mid-phase of catching up, and not able to move to the advanced level. In addition, firms are not able to network among firms in the cluster, R&D institutions and universities to bring a new wave of knowledge to transform their capabilities. By using Smart PLS the mediating effect of organizational capabilities on the relationship between technological capabilities and technology transfer, and firm performance were examined. The results show that, organizational capabilities (OC=0.484, p<0.05) mediates positively and significantly the relationship between technological capabilities and technology transfer and firm performance with the former being stronger than the latter (Direct effect TT=0.109, p=0.00 and TC=0.293, p =0.00, Indirect effect TT = 0.273, p < 0.01 and TC =0.394, p < 0.01). Hence, organizational capability partially mediates the relationship by means of strategic planning, learning by doing, marketing capabilities and knowledge management between technology transfer and technological capabilities on firm performance. The four systemic pillars used to estimate the technology upgrading index global integration showed the strongest influence (0.308) followed by network cohesion (0.255) and high-tech infrastructure (0.230), basic infrastructure (0.207) was the least influential. Moreover, management strategies (0.097) and global production networks (0.068) show the strongest impact on technological upgrading. Almost all experts emphasized the influence of producer user relationships (0.066). The technology upgrading index has a 2.3 score out of a possible 5.0, which indicates that the industry is located in the bottom half of the technology ladder. All in all, the evidence shows that existing capability development initiatives have failed to stimulate technological upgrading. The reasons for this are varied but the most crucial appears to be a lack of understanding of procedures and processes, and the inability to identify needed capabilities for development. Hence, the Pakistan government should focus on policy efforts to improve the basic and high infrastructure support while firms need to broaden their strategies to connect and expand into global value chains.